2022
DOI: 10.1002/bmc.5409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vindoline on rat cytochrome P450 isoform activities in vitro

Abstract: A specific ultra-high-performance liquid chromatography/quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF-MS/MS) method has been described for the simultaneous determination of the metabolites of tacrine, bupropion, diclofenac, dextromethorphan and midazolam, which are the five probe drugs of the five cytochrome P450 (CYP450) isoforms CYP1A2, CYP2B, CYP2C11, CYP2D1 and CYP3A4.The inhibition degree was determined by calculating the IC 50 . The chromatographic separation was performed on a C 18 column wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In the previous in vitro experiments, it was found that VDL could inhibit CYP2D1 activity, and had weak inhibitory effect on CYP2C11 and CYP3A ( S1 Fig ), which was inconsistent with the results of in vivo experiments [ 44 ]. The reasons for this phenomenon may be as follows: (1) Influence of in vivo and in vitro action time and dosage: in vitro experiments, VDL and probe drugs were directly incubated with CYP450 enzymes in rat liver microsome, while in vivo experiments, rats were pretreated with VDL for 15 days, and then the probe substrate was administered on the 16 days.…”
Section: Discussionmentioning
confidence: 69%
“…In the previous in vitro experiments, it was found that VDL could inhibit CYP2D1 activity, and had weak inhibitory effect on CYP2C11 and CYP3A ( S1 Fig ), which was inconsistent with the results of in vivo experiments [ 44 ]. The reasons for this phenomenon may be as follows: (1) Influence of in vivo and in vitro action time and dosage: in vitro experiments, VDL and probe drugs were directly incubated with CYP450 enzymes in rat liver microsome, while in vivo experiments, rats were pretreated with VDL for 15 days, and then the probe substrate was administered on the 16 days.…”
Section: Discussionmentioning
confidence: 69%